Stakeholder conflicts and forest decentralization policies in West Kalimantan: their dynamics and implications for future forest management - Yasmi, Yurdi; Anshari, G.Z.; Komarudin, Heru; Alqadrie, S. (2006)
Stakeholder conflicts in relation to forest decentralization policies were studied in West Kalimantan, Indonesia to determine: 1) how these policies were understood by local stakeholders 2) how they were implemented 3) and their impacts in terms of forest management and conflicts. A case study using qualitative methodologies i.e. semi-structured interviews, field observations and workshops, was made. The results show that the implementation of decentralization policies gave rise to conflicts between local and central government as well as among local stakeholders. Despite the goal of benefiting local stakeholders by decentralizing forest management, the central government’s subsequent withdrawal of much of the local governments’ authority to manage forestry raises new questions on whether the central government is indeed willing to share power. We concluded that central and local governments and relevant stakeholders need to develop better communication and negotiation procedures to address current conflicts appropriately.